Age and resilience amid COVID-19 pandemic adversity: the mediating roles of quality of life, spirituality, and depressive symptoms - Gonçalves, Leonardo; Reggiani, Lorenzo Casagrande; Maliuk, Josiane; de Souza, Gianfranco Rizzotto; Bandeira de Mello, Renato Gorga; Carniel, Bruno Perosa; da Rocha, Neusa Sica (Frontiers in Psychology, 2025)
IntroductionResilience scores are usually higher among older adults, but the COVID-19 pandemic and the associated social isolation in this risk group necessitate a reevaluation of this characteristic.ObjectivesTo investigate the differences in resilience among young, middle-aged, and elderly individuals and to explore the mediating factors (quality of life, spirituality, social support, depressive symptoms) in the relationship between age and resilience.MethodsA cross-sectional study was conducted in April 2020 through online collection using the snowball method, enrolling 3,278 participants. They were divided into three age groups (18–36, 37–59, 60+), and resilience was assessed using the CD-RISC-10 scale. Mediation analyses examined the roles of depressive symptoms (PHQ-9), quality of life (EUROHIS-QOL-8), spirituality (WHOQOL-SRPB), and social support (MOS).ResultsThe sample comprised 1,207 young, 1,680 middle-aged, and 391 older adults. Resilience scores were significantly higher in the elderly population compared to middle-aged and young adults [F(2,3251) = 81.12; p = 0.001]. Quality of life (β = 0.23; p = 0.001) and spirituality (β = 0.28; p = 0.001) showed positive mediating effects, while depressive symptoms (β = −0.18; p = 0.001) had a negative effect. Social support did not show a statistically significant mediating effect.ConclusionOlder age was associated with higher resilience scores, even during COVID-19 pandemic. Spirituality and quality of life were identified as mediators of this relationship. These findings underscore the need for longitudinal research to confirm whether these factors predict resilience and to guide mental health interventions.